Prototype Sistem Monitoring Kekeruhan Sumber Mata Air Berbasis Internet of Things - Udin; Heliawati Hamrul; Muh. Fuad Mansyur (Journal of Applied Computer Science and Technology, 2021)
Water is very important for the life of living things on earth. The function of water for life cannot be replaced, but water taken directly from springs often experiences turbidity which usually occurs during the rainy season where excessive rainwater intensity can affect the clarity of the water flowing into people's homes. From this problem, it is necessary to design a monitoring sistem for the turbidity of water flowing into the main tank which can be monitored via laptops, computers or cellphones that have internet access that can monitor in real-time and in the form of graphs and data stored in My Structured Query language (mysql) in this design. Using the nodemcu esp8266 which controls the tool in the design, the turbidity sensor is used to detect water turbidity, the ultrasonic sensor is used to detect the water level in the main tank, the relay is used to control the electric current, the solenoid valve is used to close the valve according to the conditions given with the design results of 120 ntu down and water height > 15 cm then the on relay and solenoid valve open the valve so that water can flow into the reservoir, while 121 ntu up and water height < 5 cm then the off relay and solenoid valve close the valve, the test is done using blackbox testing and the results of this test that the function on the sistem is 100% appropriate.